STRUKTUR ANATOMI, SIFAT FISIS DAN MEKANIS KAYU KAMBELU (Buxus rolfie Vidal.) DAN KANDURUAN (Phoebe cuneata Blume) ASAL HUTAN ALAM DI SULAWESI BARAT - Mody Lempang; Muhammad Asdar; Sri Rulliaty (BRIN Publishing, 2013)
This paper excamined the anatomical and physical properties of two wood species from West Sulawesi's natural forest, i.e. kambelu (Baccus rolfir Vidal.) and kanduruan (Phoebe cuneata Blurne). The results show that the major anatomical structure of kambelu are reddish brown beurtunod, pink greyish sapwood (2-3 cm in thickness), distinct growth rings, bard, interlocked fiber, moderately fine texture and medium lustrous surface. Wbile, kanduruan anatomical properties includes brawn greyish beartwood, light brown sapwood with 5-7 cm thickness, moderately fine and uneven texture. interlocked fiber and medium lustrous surfaces, slightly slippery, hard, no specific wood pattern and odoserless. The fiber of both wood species are classified long while the cell wall thickness are medium. Both are classified as quality 1 class for pulp and paper. Kambelu and kunduruan wood densities are 0.62 and 0,63 respectively and grouped into strength class of III-1. Shrinkage percentage of kambelu is less than kanduruan wood.